RAGAM ASESMEN DALAM PEMBELAJARAN BERDIFERENSIASI - Zahro, Amanda Lailatus; Nurdiana, Fany Meta; Melati, Nadia Vita; Setyaningsih, Sri Wahyu; Mahdiyah, Syarifah; Listiani, Welas (LPPM UNIMAL, 2025)
Differentiated learning is an approach that adapts the learning process to the needs, interests, and characteristics of students. In its implementation, assessment plays an important role in identifying students' learning needs and evaluating the effectiveness of differentiated learning. This study uses a literature study method or literature review, researchers collect data and information from various previous sources that are in accordance with the title